Enhanced methane and energy generation from sewage water using microbial fuel cells with paddy field soil substrate - Zeshan Abbas; Hafiza Yousra Bibi; Usman Khalid; Saad Saleem Khan; Stephen Larkin; Muther Mansoor Qaisrani; Ali Ahmad; Hussain Shareef; Naeem Akhtar Qaisrani (Energy Exploration & Exploitation)
Microbial fuel cells (MFCs) have potential in wastewater treatment, biogas production and clean energy generation. MFCs provide an interdisciplinary research approach incorporating engineering and natural sciences. This study explores MFCs’ capabilities to produce electricity and biogas from wastewater and field soil substrates with different compositions. A two-chamber MFC system was operated anaerobically. Household sewage water used as the organic substrate with different soil amounts. Six different process feed compositions, labeled MFC-1–6, were investigated. MFC-1 exhibited the highest biogas generation volume of 245 cm³ and 42 mW/cm² power density. MFC-5 and −6 yielded 100 cm³ and 130 cm³, respectively. Wastewater treatment was effective on day 20, with pH, conductivity, turbidity, and total dissolved solids decreased to 7.3, 2.6 mS, 326 NTUs, and 1114 mg/L, respectively. Since, MFC-1 autonomously generated −800 mV, an external battery supplied an additional 600 mV to meet the methane generation voltage requirements. MFCs’ effectiveness in addressing wastewater treatment and renewable energy production was highlighted.